Leadership: Does gender matter? - Mohamad, Nor Asiah; Mustafa, Maizatun (Serials Publications, 2012)
Question posed on women leadership are common both in Western countries and Muslim countries. There have been many researches carried out in the past, which discussed about women's ability to become a leader. In this paper, leadership of women is discussed in a broader sense, and it does not only confine to leader in an organisation or a state. In a Muslim country, appointment's of a woman as a leader is generally accepted as last choice. The issue of women leadership revolves around the competency of a women, which also includes the religious basis that woman cannot be a head of a state or women rank second to men or women biologically weak and susceptible to so many things. so, are there any differences between a woman leader and man as a leader? This paper looks at what are the unique qualities of leadership that he most effective women leaders possess, and are they unique to women only? The paper simply highlights some important common issues revolving around the topic of women leadership especially in the Muslim context, either in leading an organisation or even a political leadership based on the primary and secondary data. The special emphasis of the research is on the trend of women leadership in Malaysia and some other countries mainly Muslim countries. The basic principles of the Shari'ah on women and leadership are also highlighted. The evidence either through research data or authorities in the Shari'ah show that women are not being sidelined due to religious beliefs or because they are biologically different from men. Nowadays, reasons for not appointing men as leader are also applicable to women. The data supports that women are not appointed because they lack certain competencies and not because of their gender.